Temperature-sensitive Composite Membranes with "Double Switch" on Water Vapor Permeability (Journal of Fiber Bioengineering and Informatics, 2008)
Temperature-sensitive polymer membranes were prepared by combination of shape memoryhydrophilic polyurethane (SMPU) and thermo-sensitive poly(N-isopropylacrylamide-co-sodiumacrylate) [poly(NiPAAm-co-SA)] hydrogel micro-particles through composite coating method. Thesetwo intelligent polymer components endowed the composite membranes with &#8220double switch&#8221 on thewater vapor permeability. Poly(NiPAAm-co-SA) hydrogel micro-particles exhibited a reversible volumetransition at lower critical solution temperature (LCST) around 34-36&#176C in the experiment. The size ofgel particles varied more than 10-fold between temperature above and below LCST. It is likely acted as asensor of temperature and as an switch to regulate the water vapor permeability of composite membranes.Moreover, there was also a dramatic increase in water vapor permeability (WVP) with an increase intemperature from 35 to 40&#176C for the shape memory hydrophilic polyurethane basement membranes.Two different procedures for WVP test were employed to simulate different application situations ofthe composite membranes. The temperature-sensitive water vapor permeability of composite polymermembranes was investigated by varying the content of hydrogel micro-particles. All of the temperaturesensitivemembranes could have water vapor permeability controlled in response to temperature changes.